Exelearning como objeto de aprendizaje de Genética y Embriología con los estudiantes de séptimo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Saltos Zumba, Marianela Esthefanía (2024)
In the educational realm, it is essential to know the relationship between improvement and the use of technology. The understanding of this connection allows teachers to have various digital tools that facilitate any science’s teaching and learning process, leaving behind traditional teaching. Therefore, this research proposed learning objects using Exelearning digital tool to study Genetics and Embryology. This work used a quantitative approach, non-experimental design, descriptive, field, and bibliographical level. The researcher used the survey technique to collect data and analyze the results. Twenty-eight students took the survey in the seventh semester of the Pedagogy of Experimental Sciences, Chemistry, and Biology. All the participants were attending the Genetics and Embryology class. After analyzing and interpreting data, results suggested that using the Exelearning digital tool is recommended to elaborate learning objects given that interactive activities, virtual simulators, games, or other content have strengthened knowledge. Exelearning has also facilitated the subject’s learning process and has caused teachers and students to create a link between education and technology.